Biological Variations of Lupus Anticoagulant, Antithrombin, Protein C, Protein S, and von Willebrand Factor Assays - Shou, Weiling; Chen, Qian; Wu, Wei; Cui, Wei (Seminars in Thrombosis and Hemostasis, 2016)
The results of lupus anticoagulant (LA), antithrombin (AT), protein C (PC), and protein S (PS) testing, and the values of von Willebrand factor antigen (VWF:Ag) are important in diagnosis and therapeutic monitoring of thrombosis and hemostasis diseases. Till now, no published study has focused on the biological variations in LA testing, and only a few studies have examined the biological variations of AT, PC, PS, and VWF:Ag. With the latest fully automated instruments and improved reagents, the analytical, within-subject, and between-subject biological variations were estimated for these five coagulant parameters in a cohort of 25 apparently healthy subjects. Blood specimens were collected at 8:00 am, 12:00 pm, and 4:00 pm on days 1, 3, and 5. The analytical biological variation (CVA) values of all the parameters were less than 3%. The within-subject biological variation (CVW) and between-subject biological variation (CVG) values of the LA normalized ratio were 4.64 and 6.83%, respectively. No significant differences were observed in the intraday and interday biological variations of LA tests, or in AT, PC, PS, and VWF:Ag values. Additionally, the utility of the conventional population-based reference intervals of the five coagulation parameters was evaluated by the index of individuality, and data on CVW and CVA were used to calculate the reference change value to identify the significance of changes in serial results from the same individual.
Keywords: biological variation; thrombosis and hemostasis tests; lupus anticoagulant; index of individuality; reference change value